Towards equitable, efficient and sustainable water management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
a CTA seminar entitled Managing water equitably, efficiently and sustainably for agricultural and rural development in sub-Saharan Africa and the Caribbean which was held in Cordoba, Spain from 20 to 25 September 1999